Serbia and Montenegro : A Country Environmental Analysis - World Bank (World Bank, Washington, DC, 2020)
The specific objectives of this Country Environmental Analysis (CEA) are to: 1) Review the existing situation in the sector, identify priority areas for policy changes or investments, and consider the role of the government, the private sector, and donors in implementing this agenda 2) Assess macroeconomic-environmental linkages and measures that affect long-term sustainability and financial viability within the priority areas 3) Provide a basis for defining the Bank's future involvement in the sector. The following environmental issues have been identified as critical, based on the negative impact of the current environmental conditions on human health, the economy, and natural ecosystems: Deteriorating trends in water, sanitation, and waste management; threat of coastal zone deterioration; air pollution hot spots; energy inefficiency; excessive industrial pollution; weak environmental management system, institutionally and legally; economic instruments that are more geared to revenue generation than to providing incentives for environmentally responsible behavior; quality and quantity of water resources; transboundary water and global environmental issues; and lack of sustainable forest management. The report recommends improving waste management, particularly hazardous waste; increasing provision of basic water and sanitation services to urban and rural poor; addressing environmental hot spots; strengthening institutional capacity for environmental management; preparing a coastal zone strategy; including in the environmental assessment potential liabilities in the advent of privatization; introducing measures to enhance energy efficiency and use renewable energy sources; instituting measures to reduce nutrient run-off to the Danube; preparing a biodiversity strategy, identifying threatened species, and preparing an action plan; and preparing a management plan for Lake Skadar and introducing environmentally friendly natural resource use practices.